Cognitive and neural effects of exercise following traumatic brain injury: A systematic review of randomized and controlled clinical trials. (28th January 2020) - Sharma, Bhanu; Allison, David; Tucker, Patricia; Mabbott, Donald; Timmons, Brian W.
ABSTRACT: Objective : Sub-maximal aerobic exercise can alleviate brain injury-related symptom burden. There is substantial data from animal studies and a growing clinical evidence base to suggest that exercise may also improve cognitive and neural outcomes following brain injury. We performed this systematic review to consolidate evidence from randomized and controlled clinical trials on the effects of exercise on cognitive and neuroimaging outcomes following brain injury in humans. Design : Systematic review. Data sources : MEDLINE, EMBASE, PsychINFO, CINAHL, SPORTDiscus, and Cochrane Central Database. Eligibility criteria for screening studies : Randomized or controlled clinical trials examining the effects of exercise on cognitive and/or neuroimaging outcomes in traumatic brain injury. No restriction was placed on age (or other demographic variables) or severity of injury. Results : Six studies (with an average sample of 42 participants) met eligibility criteria. Three studies used neuroimaging and reported exercise-related improvements as measured by either functional or diffusion-based imaging. The remainder of the trials that employed cognitive outcomes reported largely null findings. Summary/Conclusion : This review demonstrates that exercise shows promise (primarily with respect to neuroimaging outcomes) as a brain injury intervention. While the field is young and heterogeneity between studies precludes meta-analysis, this review raises important questions that need to be addressed by future trials.